Does Ethical Context Affect the Ethically Related Judgement by the Observers of Earnings Management? - Feby Astrid Kesaulya; Weny Putri; - Khairunnisa (Journal of Accounting and Strategic Finance, 2019)
The aim of this research is to empirically prove that there will be a difference in ethically related judgement by the observer of earnings management, especially when they work in the company which has higher ethical context or value and they know the moral agent personally. This research used experiment to collect data by giving each respondents different treatments and scenarios. The result of this research proves that there is no different ethically related judgement from each observers in each scenarios.